Balio Sruogos Dievų miškas kaip (savita) antropologinė studija - Butkus, Vigmantas; Šeškus, Artūras (Literatūra, 2010)
The beginning of the article shortly overlooks the diversity of literary and anthropological relations. Afterwards, focus is made on some general methodological principles of socio-cultural anthropology revealed in Clifford Geertz’s, James Clifford’s, Harvey Russell Bernard’s, Vytis Čiubrinskas’s and other anthropologists’ works that are applicable for analysis of “The Forest of Gods” by Balys Sruoga.Furthermore, the article analyses “The Forest of Gods” by Balys Sruoga as a non-ordinary, specificanthropological study. Sruoga is introduced as a distinctive anthropologically-oriented observer who is “involved” in a forced procedure of participant observation. “The Forest of Gods” is compared to ethnographic texts written in a thick description manner. In conclusion the author of “The Forest of Gods” is both “a native” (a prisoner of the concentration camp experiencing all the hardships) and “an anthropologist” (who acts as an outside observer, a curious collector of information). He reflects the so-called anthropological emic viewpoint (seeing the world as an informant) as well as the etic viewpoint (having the anthropologist’s point of view). “The Forest of Gods” is an example demonstrating that, according to Paul Rabinow, the science of anthropology and fiction are to be considered not contradictory but complementary means of analysis.